Impact Digital Technology For Early Childhood Interpersonal Intelligence - Rani Nibras Idham; Mubiar Agustin (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2025)
Currently, technology is widely used by humans, including early childhood. However, technology addiction can also affect how children interact. This can result in interpersonal intelligence, lack of socialization with the surrounding environment, and impaired language development in children. Based on the above issues, the researcher aims to describe the impact of technology on the interpersonal intelligence of early childhood. This research method uses a quantitative descriptive approach with a questionnaire distributed via Google Form to 30 parents at the Nuris Raudhatul Muttaqin Early Childhood Education Center, Tanggamus, Lampung. The results show that many children already use technology, one of which is mobile phones. One of the applications that children often use is YouTube, with 15 respondents out of 30 children. Based on the data obtained, most children use mobile phones for 30 minutes. This is in line with the maximum recommended technology use for children, which is less than 1 hour under adult supervision. In addition, the results of this study found that many parents have implemented restrictions on their children's mobile phone use. They limit the time spent on mobile phones by always accompanying their children when they use the internet, setting an example in limiting mobile phone use, and redirecting them to creative activities and educational games.